Innovation output and idiosyncratic volatility: US evidence - Naji Mohammad Alshammasi; Adel Abdulkarim Almomen (Journal of Risk and Financial Management, 2023)
Firms engaging in innovative practices have patents to prevent competitive forces from eroding the resulting economic rents; however, there is limited evidence regarding the impact of innovation on risk. We shed new light on how firms' involvement in innovation activities impacts their volatility, particularly their idiosyncratic volatility. In this paper, we empirically examine the effect of innovation on idiosyncratic volatility. To do so, we empirically examine the impact of innovation, measured by patents weighted by citations and R&D expenditure, on the idiosyncratic volatility of firms. Using a large sample of 8256 US firms, we find that more innovation is associated with lower idiosyncratic volatility. We also find that information uncertainty is the channel through which innovation affects idiosyncratic risk. The results are robust for different measures of idiosyncratic volatility. These results have empirical implications for investors, managers, and firms engaging in innovation-related activities.
Keywords: D8; G12; G14; O33; 650; innovation; patents; idiosyncratic volatility; citations; information uncertainty